Anthropology of victim in postmodern cultural practices - O. A. Pushonkova, (Ukrainian Cultural Studies, 2021)
The article examines the anthropological dimension of the victim phenomenon through the prism of Rene Girard's concept and modern studies of nihilistic tendencies of cultural scenarios with dominant polar psychotypes. The significance of Rene Girard's theory in the study of the archetypal basis of victim behavior, its historical sources and myth-ritual basis is studied. The cultural specifics of modern forms of counteracting victimhood and value contradictions of the victim's figure in the conditions of new threats to humanity, changes in the space of culture in the direction of increasing dependence on media communication platforms, are revealed. Some aspects of the victim's behavior have been linked to identity patterns which suggests a hedonistic-entertaining culture format that results in narcissistic choices or escapist behavior. The article clarifies the nature of the interaction between the images of the victim in the era of multimedia communication and cultural practices which acquire the character of a ritual response to the archaic internal conflict in the context of cultural-traumatic discourse.Examining the sacred nature of the victim in the processes of desacralization of modern culture, according to R. Girard, preservation and essential transformation of this defining archetype as a medium of aggression is concluded.In the modern scenarios a model of total victim is formed that has lost the function of channeling social aggression, falling into a vicious circle of destruction of either oneself or others (W. Kraus), or which is "stuck" in the "triangle of fate", where everyone is a victim (S. Karpman).A hedonist who suffers from shortcomings in a flat everyday life, having lost the tragedy of his own existence in the culture, acts as its repressed subject, but is not aware of it, according to the psychoanalytic theory of cultural trauma. However, in everyday practices (bullying, gaslighting, trolling) anyone can be a victim at any time. In a more global dimension, we are talking about the collective nature of sacrifice, as evidenced by the tendencies of radicalism, terrorism, war, genocide, etc.It is possible to eliminate human inherent aggressive instincts only through the step-by-step development of the value sphere (W. Kraus). This is the only thing that can prevent the self-destruction of the mankind and solve the problem of intraspecific aggression, which was considered from different points of view by K. Lorentz and R. Girard.
Keywords: victim anthropology, cultural archetypes, sacrifice, victimhood, psychology of aggression, narcissism, escapism, cultural-traumatic discourse